2018
DOI: 10.1159/000495289
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Risk Factors of Venous Thromboembolism in Patients with Inflammatory Bowel Disease: A Prospective Multicenter Cohort Study

Abstract: <b><i>Background:</i></b> Venous thromboembolism (VTE) has been shown to be more frequent in inflammatory bowel disease (IBD) than in the general population in Western studies. However, the actual state of VTE in Asian IBD remains poorly understood. <b><i>Aims:</i></b> To reveal the incidence of VTE in IBD patients in Japan. <b><i>Methods:</i></b> Eighty-five patients admitted to 3 gastroenterology centers were registered from 2013 to 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…In agreement with these findings, functional proteomic profiling has recently identified cathepsin G in UC mucosa but not in CD biopsies, highlighting thus significant differences in terms of proteolytic activities and protein profiles between the most common subtypes of IBD 91 . Seeing that gut inflammation and coagulation are two inter‐dependent processes, targeting such interface has been also a major focus of research related to IBD 92‐95 . In that setting, thrombin, a serine protease released upon tissue damage, seems as a potential candidate 96 .…”
Section: Serine Proteases In Gastrointestinal Inflammationmentioning
confidence: 71%
“…In agreement with these findings, functional proteomic profiling has recently identified cathepsin G in UC mucosa but not in CD biopsies, highlighting thus significant differences in terms of proteolytic activities and protein profiles between the most common subtypes of IBD 91 . Seeing that gut inflammation and coagulation are two inter‐dependent processes, targeting such interface has been also a major focus of research related to IBD 92‐95 . In that setting, thrombin, a serine protease released upon tissue damage, seems as a potential candidate 96 .…”
Section: Serine Proteases In Gastrointestinal Inflammationmentioning
confidence: 71%
“…Few studies have previously examined the risk of VTE in Asian patients with IBD [16][17][18][19] . Most of the studies have focused on the overall risk of VTE in IBD patients compared with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, more than 50% of the reported thrombotic events were asymptomatic. 21,22 Therefore, proactive screening could be useful for early identification of thrombosis; this is especially important for thrombosis with atypical presentation such as intra-abdominal thrombosis. In our study, more patients developed intra-abdominal venous thrombosis than PE, and the reported symptoms were mostly nonspecific such as abdominal pain.…”
Section: Discussionmentioning
confidence: 99%